Cloning Gene Expression and Protein purifiation - Charles Hardin (Oxford University Press, 2001)
This combination lecture/laboratory manual presents detailed protocols for the multi-step process involved in isolating a gene, cloning and characterizing it, expressing the encoded protein, purifying the protein, and characterizing rudimentary aspects of its basic physical properties.